Control of measles in Czechoslovakia (CSSR) - Sejda, J (Reviews of infectious diseases, 1983)
Mass immunization against measles in the Czechoslovak Socialist Republic (CSSR) began in 1969 and utilized the Czechoslovak vaccine, which corresponds in its parameters to the further-attenuated measles vaccines. The immunization rate for relevant age groups of the population (i.e., children born in 1968-1980) is already 98%-99% in 1982. Measles morbidity decreased to less than 2% of the incidence before the introduction of immunization, and the mortality now is practically negligible. The decade 1972-1982 produced significant changes in epidemiologic characteristics of measles. Of importance is the gradual shift in the age distribution of affected children to older, nonimmunized age groups. Results of yearly immunologic surveys of a broad, randomly selected population sample have become the decisive criteria for evaluation of vaccine efficacy. The program of revaccination of all children was chosen as the optimal strategy for maintaining measles elimination. This program aims at ensuring a level of herd immunity in the whole population of greater than or equal to 95%.
Keywords: Czechoslovakia; Child, Preschool; Immunization, Secondary; Measles; Adolescent; Infant; Child; dítě; mladiství; vakcinace; novorozenec; předškolní dítě; sekundární imunizace; lidé; roční období; Seasons; Humans; Československo; Infant, Newborn; kojenec; Vaccination; spalničky